How to foster students' creativity? The effects of teacher subjective well-being mediation on the intellectual humility - Farida Kurniawati; Airin Yustikarini Saleh; Shahnaz Safitri (Jurnal Cakrawala Pendidikan, 2022)
Creativity is widely recognized as one of the essential skills in the 21st century. However, Indonesian students are not considered to possess this characteristic as they belong in rank 115 out of 139 countries on Global Creativity Index in 2015. This leads to the question of whether these students are fostered to think creatively, especially since Indonesian teachers are regarded to hold higher demands and workloads that might limit the attempt for encouraging creativity. This study explores this phenomenon by observing the factors enabling creativity fostering teacher behavior (CFTB). The intellectual humility possessed by the teachers is hypothesized to be predictive for the CFTB through the mediation of teacher subjective well-being. Three instruments were applied in this study: Creativity Fostering Teacher Behavior Index by Soh (2000), Intellectual Humility Scale by Porter Schumann (2018), and Teacher Subjective Wellbeing Questionnaire by Renshaw, Long Cook (2015). Data of 534 teachers from 8 provinces in Indonesia (29.2% males, 70.8 females; M-age = 39.18, SD = 10.25) showed that intellectual humility predicted the CFTB while the teacher subjective well-being served as a partial mediator.